Up‐Regulation of PKR Signaling Pathway by Ethanol Displays an Age of Onset‐Dependent Relationship. (20th September 2016) - Duncan, Jeremy W.; Johnson, Shakevia; Zhang, Xiao; Zheng, Baoying; Luo, Jia; Ou, Xiao‐Ming; Stockmeier, Craig A.; Wang, Jun Ming
Abstract : Background: Ethanol (EtOH) neurotoxicity can result in devastating effects on brain and behavior by disrupting homeostatic signaling cascades and inducing cell death. One such mechanism involves double‐stranded RNA activated protein kinase (PKR), a primary regulator of protein translation and cell viability in the presence of a virus or other external stimuli. EtOH‐mediated up‐regulation of interferon‐gamma (IFN‐ γ ; the oxidative stress‐inducible regulator of PKR), PKR, and its target, p53, are still being fully elucidated. Methods: Using Western blot analysis, immunofluorescence, and linear regression analyses, changes in the IFN‐ γ ‐PKR‐p53 pathway following chronic EtOH treatment in the frontal cortex of rodents were examined. The role of PKR on cell viability was also assessed in EtOH‐treated cells using PKR overexpression vector and PKR inhibitor (PKRI). Results: In rats chronically fed EtOH, PKR, phosphorylated PKR (p‐PKR), IFN‐ γ, and p53 were significantly increased following chronic EtOH exposure. Linear regression revealed a significant correlation between IFN‐ γ and p‐PKR protein levels, as well as p‐PKR expression and age of EtOH exposure. Overexpression of PKR resulted in greater cell death, while use of PKRI enhanced cell viability in EtOH‐treated cells. Conclusions: Chronic EtOH exposure activates the IFN‐ γ ‐PKR‐p53 pathway in the frontal cortex of rodents. p‐PKR expression is greater in brains of rodents exposed to EtOH at earlier ages compared to later life, suggesting a mechanism by which young brains could be more susceptible to EtOH‐related brain injury. PKR and p‐PKR were also colocalized in neurons and astrocytes of rats. This study provides additional insight into biochemical mechanisms underlying alcohol use disorder related neuropathology and warrants further investigation of PKR as a potential pharmacotherapeutic target to combat EtOH‐related neurotoxicity, loss of protein translation and brain injury. Abstract : Chronic ethanol exposure activates the IFN γ ‐PKR‐p53 pathway in an age‐dependent manner. p‐PKR expression is higher in brains of rodents exposed to ethanol at earlier ages compared to later life, suggesting a mechanism by which young brains could be more susceptible to ethanol‐related brain injury. This study provides insight into biochemical mechanisms underlying the onset of AUD‐related neuropathology and warrants further investigation of PKR as a potential pharmacotherapeutic target to combat ethanol‐related neurotoxicity and brain injury in adolescents.